Customer Expectations And Service Recovery As Determinants Of Loyalty: The Mediating Role Of Customer Satisfaction In Tiktok Shop By Tokopedia - Nurrohmah, Nurul; Hanif, Hanif; Nurmalia, Gustika (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines how Customer Expectation and Service Recovery affect Customer Loyalty, with Customer Satisfaction as a mediator, among TikTok Shop by Tokopedia users from an Islamic business perspective. Due to increasing e-commerce competition in Indonesia, businesses must meet expectations and recover services effectively. Using a quantitative approach, questionnaires were distributed to 96 Generation Z respondents in Bandar Lampung, and data were analyzed via SEM-PLS. Results showed Customer Expectation significantly impacts Customer Satisfaction but not directly Customer Loyalty. Service Recovery positively affects both Satisfaction and Loyalty. Satisfaction mediates between Expectation and Recovery's effect on Loyalty. Findings highlight the importance of transparency, quick recovery, and fair complaint handling to boost satisfaction and loyalty. From an Islamic view, this aligns with justice, honesty, and responsibility, aiming for long-term benefits beyond profit.